What are the barriers and facilitators to polio vaccination and eradication programs? A systematic review. - Obidimma Ezezika; Meron Mengistu; Eric Opoku; Aiman Farheen; Anuradha Chauhan; Kathryn Barrett (Public Library of Science (PLoS), 2022)
Global efforts to eradicate polio by the Global Polio Eradication Initiative agency partners and country-level stakeholders have led to the implementation of global polio vaccination programs. This study presents the findings of existing studies regarding the barriers and facilitators that countries face when implementing polio interventions. A comprehensive search was conducted in OVID Medline, OVID Embase, EBSCO CINAHL Plus, and Web of Science. Eligible studies underwent quality assessment. A qualitative evidence synthesis approach was conducted and aligned to the Consolidated Framework for Implementation Research (CFIR). The search identified 4147 citations, and following the removal of duplicates and screening according to our inclusion/exclusion criteria, 20 articles were eligible for inclusion in the review. Twelve countries were represented in this review, with India, Nigeria, Pakistan, Ethiopia, and Afghanistan having the most representation of available studies. We identified 36 barriers and 16 facilitators. Seven themes emerged from these barriers and facilitators: fear, community trust, infrastructure, beliefs about the intervention, influential opinions, intervention design, and geo-politics. The most frequently cited CFIR constructs for the facilitators and barriers were knowledge and beliefs about the intervention, followed by available resources. This study identified a wide range of barriers and facilitators to polio vaccination implementation across the globe, adding to the scarce body of literature on these barriers and facilitators from an implementation perspective and using a determinant framework. The diversity of factors among different groups of people or countries highlights the relevance of contexts. Implementers should be conversant with the contexts within which polio eradication programs boost intervention coverage and capacity. This study provides policymakers, practitioners, and researchers with a tool for planning and designing polio immunization programs. Trial registration: A protocol for this systematic review was developed and uploaded onto the PROSPERO international prospective register of systematic reviews database (Registration number: CRD42020222115).